2013
DOI: 10.2147/ijn.s37140
|View full text |Cite
|
Sign up to set email alerts
|

Infrared light-absorbing gold/gold sulfide nanoparticles induce cell death in esophageal adenocarcinoma

Abstract: Gold nanoparticles and near infrared-absorbing light are each innocuous to tissue but when combined can destroy malignant tissue while leaving healthy tissue unharmed. This study investigated the feasibility of photothermal ablation therapy for esophageal adenocarcinoma using chitosan-coated gold/gold sulfide (CS-GGS) nanoparticles. A rat esophagoduodenal anastomosis model was used for the in vivo ablation study, and three human esophageal cell lines were used to study the response of cancer cells and benign c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…One specific formulation of nanoparticles of particular interest is gold-gold sulfide nanoparticles (GGS NP). To date, GGS NP have been investigated in pre-clinical studies spanning chemotherapy delivery to tumors [ 4 ] to immuno-targeted cancer therapy and imaging [ 5 8 ]. GGS NP are reportedly advantageous over other gold formulations due to their rapid and facile one-step synthesis, superior NIR absorption efficiency (98 %) and optimal size for accumulation within tumors in vivo [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One specific formulation of nanoparticles of particular interest is gold-gold sulfide nanoparticles (GGS NP). To date, GGS NP have been investigated in pre-clinical studies spanning chemotherapy delivery to tumors [ 4 ] to immuno-targeted cancer therapy and imaging [ 5 8 ]. GGS NP are reportedly advantageous over other gold formulations due to their rapid and facile one-step synthesis, superior NIR absorption efficiency (98 %) and optimal size for accumulation within tumors in vivo [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Li and group, chitosan-coated gold/gold sulfide nanoparticles were used to treat cancer. The results suggested the ablation of cancer cells upon near-infrared irradiation of accommodated gold nanoparticles [71]. A similar stimulus was used by another research group with an organic and inorganic hybrid system of titanium carbide nanoparticles coated on pluronic F127 hydrogel.…”
Section: Photo Responsivementioning
confidence: 55%
“…et al, 2021). Li et al (2013) used chitosan coated gold/gold sulfide (CS-GGS) NPs to treat EAC through endoscopic NIR irradiation. The results showed that this treatment method could selectively target cancer cells to achieve therapeutic effects without harming normal esophageal tissue.…”
Section: Figurementioning
confidence: 99%